SERVANT LEADERSHIP AS A DIFFERENTIATOR IN INDONESIAN REGIONAL DEVELOPMENT BANK - Stefanus MS Sadana; Ign. Septo Pramesworo (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
This study aims to examine servant leadership as a differentiator in Indonesian regional development bank. It investigates the role of Human Resource (HR) leaders as a differentiator to leverage performance. The methodology used is a soft system methodology-based action research (SSM-AR). This qualitative study was conducted at South Sumatra and Bangka Belitung Regional Development Bank (Bank BSB). The findings provide a challenge to maintain sustainable growth and performance improvement services to customers. According to servant leadership theory this research gives an alternative leadership model for regional development bank. In facing global business context, this model gives the bank competitiveness to respond dynamic market that it serves, including for customers, competitors, and supplier trends.